1993
DOI: 10.1182/blood.v82.2.408.bloodjournal822408
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme therapy in Gaucher disease type 1: dosage efficacy and adverse effects in 33 patients treated for 6 to 24 months

Abstract: Gaucher disease is the most frequent lysosomal storage disease and the most prevalent genetic disease among the Ashkenazi Jews (q approximately 0.047). The disease results from inherited defects of acid beta-glucosidase and the accumulation of the substrate, glucosylceramide, in cells of monocyte/macrophage origin. The therapeutic response to macrophage-targeted (alpha-mannosyl-terminated) alglucerase (Ceredase, at 60 to 15 IU/kg every 2 weeks) was analyzed in 33 patients (age range, 2 to 63 years; 15 splenect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 0 publications
0
25
0
2
Order By: Relevance
“…1993; Weinreb et al 2002) describe the effects of alglucerase/ imiglucerase treatment after 6 months to 5 years. Pastores et al (1993) and Weinreb et al (2002) reported improvements in all hematological and visceral organ parameters within the first 6 months to 2 years of therapy. Specifically, Weinreb et al (2002) reported that patients with anemia achieved normal hemoglobin levels within 2 years of starting imiglucerase, and hemoglobin levels were sustained or increased during the initial 5 years of therapy.…”
Section: Discussionmentioning
confidence: 95%
“…1993; Weinreb et al 2002) describe the effects of alglucerase/ imiglucerase treatment after 6 months to 5 years. Pastores et al (1993) and Weinreb et al (2002) reported improvements in all hematological and visceral organ parameters within the first 6 months to 2 years of therapy. Specifically, Weinreb et al (2002) reported that patients with anemia achieved normal hemoglobin levels within 2 years of starting imiglucerase, and hemoglobin levels were sustained or increased during the initial 5 years of therapy.…”
Section: Discussionmentioning
confidence: 95%
“…Enzyme replacement therapy (ERT) for patients with Gaucher disease was first introduced in 1991 [28] as a placenta-derived product [29] and then in recombinant form [30,31]; each has proven to be effective in management of the key disease parameters including reduction in organomegaly, improvement in hematological and biochemical parameters, decrease in bone-related pain, and compensatory growth in children. However, ERT probably cannot reverse nor halt the course of preexisting destructive skeletal complications [32].…”
mentioning
confidence: 99%
“…ERT with alglucerase (Ceredase) or imiglucerase (Cerezyme) has been shown to result in hematopoietic reconstitution and reduction of hepatosplenomegaly (27). However, its effect on lung involvement remains to be established.…”
Section: Discussionmentioning
confidence: 99%